Military and Negotiation : the Role of the Soldier/Diplomat. - Goodwin, Deborah (Taylor & Francis, 2004)
An investigation of the role of the modern soldier/diplomat and the nature of military negotiation in comparison with negotiation in other contexts. An analysis of the role of the military in current operations as negotiators and liaison workers in.